Characteristics of a hard cheese manufactured using high heat-treated sheep or mixed sheep-goat milk. - Pappa, EC; Kondyli, E; Vlachou, A-M; Malamou, E (Journal of the Hellenic Veterinary Medical Society, 2025)
The cheese-making conditions of hard cheeses produced from high heat treatment of sheep (S) milk or mixture of sheep-goat (SG) milk (50:50) from a mountainous area were studied. The cheeses were assessed for their composition, biochemical, textural and organoleptic characteristics during ripening and storage. The manufacturing technology included heating of milk at high temperature (90oC for 15 min), addition of starter culture at 45oC, clotting the milk with rennet, cutting and scalding-up at 47-48oC, pressing, salting in brine, ripening at 16-18oC for 30 days and storage up to 180 days. The cheese had a yellow crust, a compact texture and a pleasant flavour. The moisture of the cheeses (30-180 days), regardless of the type of milk used, ranged from 34.89% to 30.24% and the fat-in-dry matter (FDM) content was from 54.28% to 50.04%. The above results indicate that cheeses of the present study were classified as hard cheeses (referred as those with maximum moisture content 38%) of excellent quality (maximum moisture 35% and minimum FDM 47%), according to the Greek legislation. Generally, nitrogenous fractions and total free fatty acids content increased during ripening and storage, regardless of the type of milk used. In general, no differences were observed in the composition and the biochemical characteristics of S and SG (50:50). The cheeses manufactured using SG milk were harder (P<0.05) than S cheeses at 60 and 90 days of ripening and storage. The antioxidant activity of the cheeses ranged from 49.65 to 58.82 2,2-diphenyl-1 picrylhydrazyl % percentage of radical scavenging activity regardless of the type of milk used and the different sampling dates. High scores were obtained during the organoleptic evaluation, for both cheeses. In conclusion, using high heat treated milk and the present manufacturing technology an excellent quality hard cheese can be produced.